A normative theory of the information society - Duff, Alistair S., 1961- (New York : Routledge, 2012)
"There is a clear need for a systematic, integrative, and rigorous normative theory of the information society. In this book, Duff offers a prescriptive theory to help to guide the academic and policy communities as they debate the future shape of emerging post-industrial, information-based societies. He argues that information policy needs to become anchored in a left-liberal philosophy which foregrounds a feasible permutation of the core ideals of freedom, equality and brotherhood. The information society, if it is to be worth having at all, cannot be allowed to be largely the outcome of the free play of market forces and technological determinism. The social structure, including the information economy, must be subjected to a regulatory axiological system as explicated by some leading proponents of social democracy"--
1. The need for a normative theory of the information society -- 2. Reloading social democracy : a Rawls-Tawney synthesis -- 3. On the social distribution of information and news -- 4. Social engineering : industrial and post-industrial.
Includes bibliographical references (p. [131]-150) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Information society; Electronic books